Photocatalytic Aminodecarboxylation of Carboxylic Acids. Issue 20 (19th June 2016) - Lang, Simon B.; Cartwright, Kaitie C.; Welter, Richard S.; Locascio, Theresa M.; Tunge, Jon A.
Abstract : Aminodecarboxylation of unactivated alkanecarboxylic acids has been accomplished utilizing an organic photocatalyst. This operationally simple reaction utilizes readily available carboxylic acids to chemoselectively generate reactive alkyl intermediates that are not accessible via conventional two‐electron pathways. The organic radical intermediates are efficiently trapped with electrophilic diazo compounds to provide aminated alkanes. Abstract : Aminodecarboxylation of unactivated alkanecarboxylic acids has been accomplished utilizing an organic photocatalyst. This operationally simple reaction utilizes readily available carboxylic acids to chemoselectively generate reactive alkyl intermediates that are not accessible via conventional two‐electron pathways.